MECHANICAL PROPERTIES OF KENAF/GLASS FIBRE REINFORCED UNSATURATED POLYESTER HYBRID COMPOSITES: EXPERIMENTAL AND LS-DYNA SIMULATION INVESTIGATION - Alaseel B.; Nainar M.A.M.; Nordin N.A.; Rahim M.N.A.; Topa A. (Taylor's University, 2025)
Recently, there has been a strong tendency towards minimising environmental contamination through the use of less synthetic fibre in industrial applications. Hybridizing natural and manmade fibres is an intriguing method for strengthening composite materials particularly for high performance applications. Kenaf/glass fibre hybrid composites provide an excellent balance of mechanical properties, physically light weight, and low cost. In electrical applications, glass fibre reinforced polymer (GRP) insulator rods are rapidly displacing porcelain rods due to their inherent properties. This study is aimed at developing kenaf/glass fibre hybrid reinforced unsaturated polyester (UPE) and to investigate its mechanical properties. Different additions and arrangement profiles of kenaf/glass fibres were used as reinforcement in polyester resin via the pultrusion process. Tensile strength of the hybrid composite showed that adding 30 vol% of kenaf fibre resulted in a notable improvement compared to the pure glass, which is an important characteristic of an electrical insulator for power transmission line. The LS-DYNA simulation results for the mechanical strength were more than 96.5 % accurate; thus, the model can be relied upon. ? School of Engineering, Taylor?s University.